Reassessing competition concerns in electronic communications markets - Martin Peitz; Tommaso Valletti (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2014)
Central features of today's electronic communications markets are complementarities between the different layers of the value chain, substitutability between some applications, network effects in the provision of content and services, two-sided business models that partly involve indirect revenue generation (such as advertising and data profiling), and a patchwork of regulated and unregulated segments of the market. This complexity requires a fresh look at the market forces shaping the industry and a rethinking of market definitions and of the assessment of market power. This article presents the state of play in European electronic communication markets, with a particular emphasis on the recent development of 'over the tops'. We also use a stylised model of an electronic communications market to draw some central lessons from economic theory and to elaborate on market definition and market power.
urn:nbn:de:bsz:180-madoc-373977
Keywords: D82; L13; L41; L51; L86; L96; 330; telecommunications; OTT; relevant market; two-sided markets; market power